Analysis of Physiochemical and Functional Properties of Oat-Based Synbiotic Beverage Enriched with Phytonutrients - Pal, A. D.; Bhowal, S. (Journal of Scientific Research, 2023)
Synbiotic food and beverages incorporate a synergistic combination of probiotics and prebiotics to foster enhanced health benefits compared to their individual counterparts. The present study analyzed the physiochemical and functional properties of a synbiotic beverage prepared with a combination of Lactobacillus casei as probiotic and oats as the prebiotic substrate versus L. casei (5 %) in the dairy matrix as control (C). This low-fat and hypo-caloric product was enriched with whey proteins and natural colors to enhance its favorable effects. Sensory analysis depicted variation 2 (V2) to manifest increased acceptance (8.0±0.2) and the highest count of viable probiotics (8.5×1011±82) versus the other variants. V2 exhibited a significant content of proximate components, dietary fiber (TDF), and polyphenols along with an optimum organic acid production (88±0.3), titratable acidity (1.6±0.3), pH (4.3±0.2), and enhanced antioxidant capacity portrayed by reducing power (25 ± 0.9 mg/mL) and H2O2 scavenging abilities (157.5±6.1 µg/mL) as well as improved survival in the in vitro simulated gastrointestinal environment compared to the control. Additionally, V2 revealed a shelf life of 28 days at refrigerated storage (4-6 °C) with suitable retention of organoleptic characteristics, acidity, and viability. Hence, the developed synbiotic and polyphenol-enriched beverage may impart beneficial health effects through its nutritional and functional properties.